Harmonization of Islamic Values and Local Wisdom in The Maccera Manurung Ritual - Rian Hidayat; Zulhas'ari Mustafa; La Ode Ismail Ahmad; Nabiha Amaliah Iqbal (El Harakah)
The Maccera Manurung ritual is a vital part of life for the Labuku community, fostering harmony among humans, nature, and spiritual beliefs. A key challenge lies in preserving this tradition while adhering to religious principles and bridging the gap between deeply rooted local customs and Islamic values that guide contemporary society. This study adopts a qualitative descriptive approach, incorporating normative sharia, historical, phenomenological, and sociological perspectives. Data were collected through observation, interviews, and documentation. The findings indicate that the Maccera Manurung ritual reflects values that harmonize Islam and local wisdom, including: (1) spiritual and religious values that frame the ritual as an act of worship, (2) solidarity and mutual cooperation values that strengthen social cohesion, (3) respect for ancestors as recognition of spiritual heritage, (4) simplicity values that counter materialism, and (5) social responsibility values aligned with Sharia principles. Future research should expand its focus to explore other local traditions that integrate religious and cultural values, further enriching understanding in this field.